Risk Factors Predicting Chemotherapy-induced Severe Neutropenia and Outcome in Advanced Stage Non-small Cell Lung Cancer: Data from the Limited Resource in Thailand - Neesanun, Sunee (Asian Pacific Journal of Cancer Care, 2022)
Introduction: Chemotherapy-induced severe neutropenia requires dose reduction, delay in treatment, or discontinuation, and induces neutropenic complications resulting in poor outcomes and increased healthcare costs. This study aims to identify the risk factors for chemotherapy-induced severe neutropenia and outcome in advanced-stage NSCLC. Method: From July 2014-January 2019, advanced-stage NSCLC who received chemotherapy were retrospectively analyzed. Demographic and risk factors data were collected from the electronic medical record system. Univariate and multivariate logistic regression analyses were performed to identify risk factors for severe neutropenia. Survival curves were estimated using the Kaplan–Meier method. Results: Among 259 patients, 37 (14.28%) and 3 patients (1.2%) developed severe neutropenia and febrile neutropenia respectively. In multivariate analysis, restriction of protein diet (OR 9.54; 95%CI 2.44-37.24; P=0.001), concomitant use herbal medicine (OR 8.66; 95% CI 1.04-72.07; P=0.045), high BMI (OR3.1; 95% CI 1.07-8.99; P=0.04), renal disease (OR 3.9; 95% CI 1.7-8.91; P=0.001), number of cycle chemotherapy > 4 (OR 3.97; 95% CI 1.11-14.18; P=0.03) were significant predictors of Chemotherapy-induced severe neutropenia. No difference in response rate, progression-free survival and overall survival among groups (RR 18.9% vs 26.7%; median PFS; 9.6 vs 8.2 months, P=0.32 and median OS 13.8 vs 16.7 months, P=0.79 in severe and non-severe neutropenia respectively). Conclusions: The present study indicates that protein-restricted diet, concomitant use of herbal medicine, BMI ≥ 25 kg/m2, renal disease, and more than 4 cycles of chemotherapy are significant risk factors for chemotherapy-induced severe neutropenia. Therefore, patients with these risk factors should be more carefully monitored.